The Influence Of Picture Series In Teaching Speaking Recount Text - Mutiara Rahmadania; Sayid Ma’rifatulloh (Pusat Riset dan Inovasi Nasional, 2023)
This research is a research to test whether the use of picture series media is influence in teaching writing. The purpose of this study was to determine whether there was a significant difference in the writing ability of students who were taught using the picture series. The population of this research is the eighth grade students of MTs Nurul Qur'an Jogoroto in the academic year 2022/2023. The total population is 215 students divided into six classes, each class contains between 35-38 students. The sample in this study was class VIII 5 and VIII 6 MTs Nurul Quran Jogoroto, totaling 70 students. The researcher used Quasi Experimental Class method to obtain score data. The researcher conducted a normality test to find out whether the data was normal or not. Based on the data normality test that has been carried out by the researcher, it shows that sig. 2-tailed is 0.000 meaning that data is normally distributed. Then, it will be continued with a mann whitney test. Based on the testing the hypothesis terms, if score of t is sig. < 0.05, Ha is accepted and H0 is rejected. In the mann whitney test calculation, the data shows sig.(2-tailed) 0.000. The data lower than 0.5, it means that H0 is rejected and Ha is accepted.